The Effect of Job Search Requirements on Welfare Receipt - Nicolas Herault; Ha Vu; Roger Wilkins (Institute of Labor Economics (IZA), 2020)
Many countries impose job search requirements on unemployment benefit recipients. Existing studies have evaluated only incremental changes to requirements. Australian reforms in 1995 saw groups of welfare recipients newly subjected to job search requirements, allowing us to produce the first causal estimates of the total effects of such requirements on welfare receipt. Using a quasi-experimental design and administrative data, we find large negative effects on welfare receipt for the mature-age partnered women targeted by the reforms. We also find large negative effects on welfare receipt of their partners, suggesting family labour supply decisions were considerably affected.
Keywords: H31; D10; J65; 330; welfare receipt; unemployment benefit; job search requirements